(untitled) (Medicine Today, 2022)
Introduction & objective: Dengue is an acute illness caused by Aedes mosquito, commonly caused by Aedes aegypti. It is an endemic disease in South East Asian countries especially in Bangladesh. In 2019 a outbreak occurred in Bangladesh. The objective of the study was to see the laboratory parameter and outcome of dengue fever in a tertiary medical college hospital. Early diagnosis and laboratory investigations is essential to prevent the mortality associated with this disease. Materials & Methods: This prospective study was conducted on dengue ward at Khulna medical college hospital from 1 July 2019 to 31 December 2019. The diagnosis of dengue infection was confirmed by serology. Sera were processed by dengue ELISA. Investigations like haemoglobin estimation, haematocrit, platelet count, total count; differential leukocyte count, peripheral smear, coagulation profile were performed. Results: Total number of cases was 98. Of them 62 (63.2%) was male and 36 (36.73%) was female. Fever was most common (100%) manifestation and duration of fever ranges from 5 to 8 days with a mean duration of 6.31 (± 0.95) days. Blood for NS1 was positive in 90 (91.83% ) cases; most cases 71 (72.44%) become positive between 2nd to 4th day. 90 (91.83%) cases developed thrombocytopenia and it starts at 5th day in 45 (45.91%) cases. Anti IgM was positive in 4 (4.08%) cases; 2 at 4th day and 2 at 5th day of illness. IgG was positive in case at 8th day of illness. Conclusion: These findings help physicians in early diagnosis of dengue by suspecting these features as of dengue and can prevent morbidity and mortality associated with dengue. Medicine Today 2022 Vol.34(1): 61-64